Determinants of Firm Value with Financial Performance as Moderating Variable - Aminda, Renea Shinta; Timur, Bintang; Purnahayu, Indu; Yulia, Eka; Maftukha, Maidatun (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2022)
Intellectual capital, measured by VACA, VAHU, STVA, is several factors that influence fluctuations in firm value. This study uses a moderating variable with the ROA ratio to determine whether intellectual capital plays a significant role in increasing firm value. Data analysis used quantitative descriptive methods with Eviews 10 on Property and Real Estate sectors listed on the Indonesia Stock Exchange in 2017-2019. The results showed the importance of the role of Intellectual VACA, VAHU, STVA simultaneously having a significant effect on Firm Value (PBV) and Company Performance (ROA) but failed to moderate VAHU, STVA, and VACA in 16 companies.